Peran Polri Dalam Menanggulangi Premanisme Di Karanganyar - Ardi, Utuh Panggayuh; , Sudaryono, SH., M.Hum; , Kuswardani, SH., M.Hum (2015)
The purpose of this study was to: 1) describe the forms of thuggery that occurred in Karanganyar; 2) describe and analyze the role of the police in preventing the occurrence of thuggery in Karanganyar in accordance with Law No. 2 of 2002 on the Indonesian National Police; 3) analyze the factors that become obstacles for the police in tackling hooliganism in Karanganyar. This research includes empirical juridical ie an approach which refers to the rules written to then see how the implementation on the ground. Research conducted at the Police Karanganyar. Source of data using primary data from interviews and observations. Data were analyzed using qualitative analysis. The results showed that: 1) Forms Karanganyar thuggery which occurred in the form of a case of extortion, bribery, carrying weapons, assault, and fights; 2) Ensure that the response to the Police thuggery Karanganyar take preventive manner (extension), repressive (action), and preemptive (ward); 3) Barriers for the police in tackling hooliganism in Karanganyar: public awareness, witnesses fear, skepticism society. The solution to these obstacles is wearing a strict legal penalties and justice to the perpetrators of the crime, preservation and continuity of the value of the norm in society, provide skills training for criminal or unemployment.